Effect of accelerated portland cement-chitosan on dentinogenic/osteogenic differentiation of stem cell from human exfoliated deciduous teeth - Yasin, Zahidah Nasuha Mohd (2020)
Mineral trioxide aggregate (MTA) is a recent gold standard endodontic biomaterial but its application is limited by expensive cost, long setting time and can cause cell toxicity. To overcome this problem, the discovery and development of new potential biomaterial is crucially required. Hence, in this study we determined the effects of accelerated Portland cement-chitosan (APC-CHT) on the dentinogenic and osteogenic differentiation in stem cells from human exfoliated deciduous teeth (SHED). The APC-CHT was prepared 1 week prior to the treatment on SHED for 14 days. The cell morphology was accessed using an inverted microscope. SHED demonstrated phenotype transition from fibroblast-like to extended-spindle morphologies starting from Day 7 until Day 14. The highest protein concentration obtained through Bradford assay was 16.89 mg/ml which is in group 4 (APC-2.5 % CHT). The sizes of proteins in this study i.e. OCN, GAPDH, ALP, DMP-1, MEPE, OPN and DSPP were evaluated using SDS-Polyacrylamide Gel Electrophoresis (SDS-PAGE). The highest band intensity was observed in Day 14 in group 3 (APC-1.25 % CHT) and 4 (APC-2.5 % CHT). Western blot analysis also demonstrated the appearance of apparent bands in Day 14 in both group 3 and 4. In conclusion, APC-CHT exhibited favourable effects on dentinogenic/osteogenic differentiation in SHED and has the potential to be used as an alternative material in dental applications.